Community Empowerment through Posyandu: “My Healthy Plate”, Sidenreng Rappang Regency - Nasrayanti Nurdin; Nurjanna Nurjanna; Fatmawati Fatmawati (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2026)
The " fill my healthy plate " program is a strategic effort to improve public health status through a family-based promotive and preventive approach. Many families do not understand the importance of food composition that meets the body's nutritional needs, so diets tend to be high in carbohydrates, low protein, and lack of intake of vegetables and fruits. This condition is further exacerbated by limited access to nutrition information and education that is practical and easy to apply in daily life. The concept of "fill my healthy plate" serves as a simple guideline that replaces the old concept of "four healthy five perfect" by emphasizing the proportion of food on a single plate: half of the plate is made up of vegetables and fruits, while the other half is made up of carbohydrate and protein sources. Although this concept has been widely introduced, its implementation at the household level is still not optimal. This service emphasizes a participatory educational approach through counseling, demonstration and hands-on practice methods. This service has a target for housewives who have toddlers or teenagers who are members of the Posyandu Asri 1 area. Education is carried out through leaflets, posters and presentation materials. The results of the service show an increase in knowledge about balanced nutrition and the concept of "fill my healthy plate". The community is able to arrange the composition of food accordingly. Through this program, the education provided not only increases knowledge but also forms attitudes and behaviors that support a healthy lifestyle